Disproportional signal of pericarditis with biological diseasemodifying antirheumatic drugs (bDMARDs) in patients with ankylosing spondylitis: a disproportionality analysis in the FAERS database - Xia, Shuang; Li, Yun-Fei; Raschi, Emanuel; Zhang, Bi-Kui; Noguchi, Yoshihiro; Sarangdhar, Mayur; Yan, Miao; Ma, Jin-An (Frontiers in Pharmacology, 2024)
The study aimed to investigate the potential association between biological disease-modifying antirheumatic drugs (bDMARDs) and pericarditis and to uncover relevant clinical characteristics in Ankylosing Spondylitis (AS).Methods: Reports of pericarditis recorded in the FDA Adverse Event Reporting System (FAERS) (January 2004-December 2022) were identified through the preferred term "pericarditis". Demographic and clinical characteristics were described, and disproportionality signals were assessed through the Reporting Odds Ratio (ROR) and Information Component (IC). A significant signal was detected if the lower bound of IC (IC025) is more than zero.We found 1874 reports of pericarditis with bDMARDs (11.3% of cases with fatal outcome). Adalimumab (IC025 3.24), infliximab (IC025 4.90), golimumab (IC025 5.40), certolizumab (IC025 5.43), etanercept (IC025 3.24), secukinumab (IC025 3.97) and ustekinumab (IC025 7.61) exhibit significant disproportionality signals compared to other medications in FAERS database. After excluding pre-existing diseases and cotreated drugs that may increase the susceptibility of pericarditis, the disproportionality signal associated with infliximab, certolizumab, etanercept, secukinumab and ustekinumab remained strong. Pericarditis cases associated with all bDMARDs were predominantly recorded in females and aged 25-65 years.More reports of pericarditis were detected with AS patients on bDMARDs than with other drugs in the overall database. Further studies are warranted to investigate the underlying mechanisms and identify patient-related susceptibility factors, thus supporting timely diagnosis and safe(r) prescribing of bDMARDs.